PHOTOISOMERIZATION OF 1-VINYL-7,7- DIMETHYL BICYCLO [2.2.1] HEPTA-ZONE (Journal of Sciences, Islamic Republic of Iran)
The acetone sensitized photolysis of the title compound gave 2-(2- oxopropy1)-9,9- dimethyl bicyclo [3.3.l]nona-3-one. A bridgehead cyclopropane intermediate was then suggested for the formation of the photoproduct